Charge‐Induced Unzipping of Isolated Proteins to a Defined Secondary Structure. Issue 10 (5th February 2016) - González Flórez, Ana Isabel; Mucha, Eike; Ahn, Doo‐Sik; Gewinner, Sandy; Schöllkopf, Wieland; Pagel, Kevin; von Helden, Gert
Abstract: Here we present a combined experimental and theoretical study on the secondary structure of isolated proteins as a function of charge state. In infrared spectra of the proteins ubiquitin and cytochrome c, amide I (C=O stretch) and amide II (N–H bend) bands can be found at positions that are typical for condensed‐phase proteins. For high charge states a new band appears, substantially red‐shifted from the amide II band observed at lower charge states. The observations are interpreted in terms of Coulomb‐driven transitions in secondary structures from mostly helical to extended C5 ‐type hydrogen‐bonded structures. Support for this interpretation comes from simple energy considerations as well as from quantum chemical calculations on model peptides. This transition in secondary structure is most likely universal for isolated proteins that occur in mass spectrometric experiments. Abstract : Ultracold gas‐phase IR spectroscopy reveals that highly charged protein ions adopt highly ordered, regular secondary structures that are characterized by intramolecular C5 hydrogen bonds. This transition in secondary structure is supported by a simple electrostatic model and is most likely universal for isolated proteins.